Song as a pursuit-deterrent signal, and its occurrence relative to other anti-predation behaviours of skylark (Alauda arvensis) on attack by merlins (Falco columbarius) - Cresswell, Will (Behavioral Ecology and Sociobiology, 1994)
Skylarks show a range of anti-predation behaviours including flocking, refuge-seeking and song. Responses by skylarks to merlin attack were recorded over three winters on a Scottish estuary to determine the effectiveness of song as a pursuit-deterrent signal, and its use with respect to other anti-predation options such as flocking. Mortality due to merlin predation was high. Skylarks used song as a pursuit-deterrent signal. Merlins chased non- or poorly singing skylarks for longer periods compared to skylarks that sang well. A merlin was more likely to catch a non-singing than a poorly singing than a full-singing skylark. Temperature did not affect chase lengths, song types or success rates of attacks. Larger flocks of skylarks were preferentially attacked so that the individual probability of being attacked within some larger flock sizes was greater than in a smaller flock. Success rate did not vary with flock size. Merlins chose skylarks before any song was heard, so there was no cost for non-singing skylarks in joining flocks. The frequency of capture on merlin attack depended on the escape response used by the skylark. Non-singing skylarks were probably more likely to escape by seeking a refuge or staying on the ground on attack, while singing skylarks were more likely to escape if they flew. The optimal escape option available to a skylark on merlin attack was probably dependent on its condition, as indicated by its ability to sing on attack.